Coexistência adaptativa entre WI-FI e 5G NR-U utilizando múltiplas numerologias para atender a equidade do 3GPP - Tsuchiya, Lucas Buzetto (2025)
This work focuses on the analysis of the crucial parameters for effective coexistence between Wi-Fi and 5G NR-U networks, based on the guidelines of the 3GPP standard. Given the importance of both technologies to meet the growing demand for connectivity, and considering the 3GPP Release 16 report that emphasizes the need for 5G NR-U to operate in unlicensed spectrum without compromising preexisting services such as WiFi, this study aims to investigate solutions to ensure harmonious and fair coexistence. The main objective is to contribute to the understanding of the challenges and solutions related to the efficient and equitable sharing of unlicensed spectrum between private 5G networks and Wi-Fi. To this end, the work is structured in three stages: survey and analysis of existing sharing methods, assessment of the impact of technical coexistence parameters (with emphasis on 5G numerologies), and numerical validation through simulations to compare different strategies and their effects on spectral efficiency and quality of service.